Monitoring macroplastics in aquatic and terrestrial ecosystems: Expert survey reveals visual and drone-based census as most effective techniques - L. Gallitelli; P. Girard; U. Andriolo; M. Liro; G. Suaria; C. Martin; A.L. Lusher; K. Hancke; MCM Blettler; O. Garcia-Garin; I.E. Napper; L. Corbari; et al. (Science of The Total Environment, 2024)

OS01-01 Exploring extracellular and Intracellular interactions and effects of advanced materials on reconstituted primary human bronchial epithelial cultures and connecting their potential impacts on lung health - Z. Wang; J. Vernaz; M. Stange; N. Tagaras; A. Meyer-Plath; T. Buerki-Thurnherr; V.M. Kissling; S. Constant; G. Gupta; P. Wick (Toxicology Letters, 2024)

Overexpression of the UDP-glycosyltransferase UGT34A23 confers resistance to the diamide insecticide chlorantraniliprole in the tomato leafminer, Tuta absoluta - Charles Grant; Kumar Saurabh Singh; Angela Hayward; Benjamin J. Hunt; Bartlomiej J. Troczka; Adam Pym; Seung-Joon Ahn; Bin Zeng; Cong-Fen Gao; Alicia Leroux; Eve Daum; Philip Süess; et al. (Insect Biochemistry and Molecular Biology, 2023)

Pseudomonas aeruginosa isolates defective in function of the LasR quorum sensing regulator are frequent in diverse environmental niches - Marie‐Christine Groleau; Hélène Taillefer; Antony T. Vincent; Philippe Constant; Eric Déziel (Environmental Microbiology, 2022)
Summary The saprophyte Pseudomonas aeruginosa is a versatile opportunistic pathogen causing infections in immunocompromised individuals. To facilitate its adaptation to a large variety of niches, this bacterium exploits population density‐dependent gene regulation systems called quorum sensing (QS). In P. aeruginosa , three distinct but interrelated QS systems ( las , rhl and pqs ) regulate the production of many survival and virulence functions. In prototypical strains, the las system, through its transcriptional regulator LasR, is important for the full activation of the rhl and pqs systems. Still, LasR‐deficient isolates have been reported, mostly sampled from the lungs of people with cystic fibrosis, where they are considered selected by the chronic infection environment. In this study, we show that a defect in LasR activity appears to be an actually widespread mechanism of adaptation in this bacterium. Indeed, we found abundant LasR ‐ defective isolates sampled from hydrocarbon‐contaminated soils, hospital sink drains and meat/fish market environments, using an approach based on phenotypic profiling, supported by gene sequencing. Interestingly, several LasR‐defective isolates maintain an active rhl system or are deficient in pqs system signalling. The high prevalence of a LasR‐defective phenotype among environmental P. aeruginosa isolates questions the role of QS in niche adaptation.

Characterization of the fungal flora of dolo, a traditional fermented beverage of Burkina Faso, using MALDI-TOF mass spectrometry - Bamba Sanata; Zida Adama; Sangaré Ibrahim; Sondo Apoline; Cissé Mamoudou; Sirima Constant; Guiguemdé T. Robert; Hennequin Christophe (World Journal of Microbiology and Biotechnology, 2017)

Chemical Speciation of Copper in a Salt Marsh Estuary and Bioavailability to Thaumarchaeota - Hannah Whitby; James T. Hollibaugh; Constant M. G. van den Berg (Frontiers in Marine Science, 2017)

Toward a Quality-Controlled and Accessible Pitzer Model for Seawater and Related Systems - David R. Turner; Eric P. Achterberg; Chen-Tung A. Chen; Simon L. Clegg; Vanessa Hatje; Maria T. Maldonado; Sylvia G. Sander; Constant M. G. van den Berg; Mona Wells (Frontiers in Marine Science, 2016)

Plant Species Diversity in the Southern Part of the Taï National Park (Côte d’Ivoire) - T. Steve Denguéadhé Kolongo; Guillaume Decocq; Constant Y. Adou Yao; Edy C. Blom; Renaat S. A. R. Van Rompaey (Biodiversity and Conservation, 2006)

Detailed analysis of the geometric relationship between external traits and the shape of red heartwood in beech trees (Fagus sylvatica L.) - H. Wernsdörfer; T. Constant; F. Mothe; M. A. Badia; G. Nepveu; U. Seeling (Trees, 2005)

Bioavailability of Reversibly Sorbed and Desorption-Resistant 1,3-Dichlorobenzene from a Louisiana Superfund Site Soil - Sangjin Lee; R. R. Kommalapati; K. T. Valsaraj; J. H. Pardue; W. D. Constant (Water, Air, & Soil Pollution, 2004)

Rate-Limited Desorption of Volatile Organic Compounds from Soils and Implications for the Remediation of a Louisiana Superfund Site - Sangjin Lee; R. R. Kommalapati; K. T. Valsaraj; J. H. Pardue; W. D. Constant (Environmental Monitoring and Assessment, 2002)

Soil-Water Partitioning and Desorption Hysteresis of Volatile Organic Compounds from a Louisiana Superfund Site Soil - R. R. Kommalapati; K. T. Valsaraj; W. D. Constant (Environmental Monitoring and Assessment, 2002)

Partition Constants and Adsorption/Desorption Hysteresis for Volatile Organic Compounds on Soil from a Louisiana Superfund Site - Kalliat T. Valsaraj; Raghava R. Kommalapati; Edward D. Robertson; W. D. Constant (Environmental Monitoring and Assessment, 1999)